Preparation of β-Ni (OH)2 Nanosheet–Modified Glassy Carbon for Pseudocapacitors - Putra, Muhammad Buchari Setia; Aliyah, Aliyah; Sanjaya, Afiten Rahmin; Pramadewandaru, Respati Kevin; Chung, Hoeil; Ivandini, Tribidasari Anggraningrum (UI Scholars Hub, 2024)
β-Nickel hydroxide (Ni(OH)2) nanosheet–modified glassy carbon for pseudocapacitors was successfully prepared. The nanosheets were synthesized via a conventional growth seeding method combined with hydrothermal treatment. Transmission electron microscopy (TEM) characterization indicated the hexagonal structure of the nanosheets of around 15 nm in size, and X-ray diffraction (XRD) pattern confirmed the β-phase lattice crystal. These nanosheets used to modify the glassy carbon surface, increased the electroactive surface area by around 15 times. Furthermore, electrochemical investigation of the modified glassy carbon revealed an excellent performance and a specific capacitance of 628.01 F g−1 at a 1 A g−1 current density. Moreover, an outstanding stability was demonstrated, with 89.9% retention of the capacitance observed after 3000 cycles at a 1 A g−1 current density.